INFORMATION TECHNOLOGY OPTIMIZATION MODES OPERATION USING GAS MAIN PIPELINE AND UNDERGROUND STORAGE - Крихівський, Михайло Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Powered principles of information technology for optimization of the gas main using underground storage. Information technology optimization of the criterion of minimizing required power compressor station. It uses a mathematical model to determine the optimal technological parameters of underground gas storage in the ring during its operation.